Hepatitis E seroprevalence in the Americas: A systematic review and meta‐analysis. (3rd May 2018) - Horvatits, Thomas; Ozga, Ann‐Kathrin; Westhölter, Dirk; Hartl, Johannes; Manthey, Carolin F.; Lütgehetmann, Marc; Rauch, Geraldine; Kriston, Levente; Lohse, Ansgar W.; Bendall, Richard; Wedemeyer, Heiner; Dalton, Harry R.; et al.
Abstract: Background & Aims: While hepatitis E virus infections are a relevant topic in Europe, knowledge about epidemiology of hepatitis E virus infections in the USA and Latin America is still limited. Aim of this study was to estimate anti‐hepatitis E virus IgG seroprevalence in the Americas and to assess whether low socioeconomic status is associated with hepatitis E virus exposure. Methods: We performed a systematic review and meta‐analysis. Literature search was performed in PubMed for articles published 01/1994‐12/2016. Prevalence was estimated using a mixed‐effects model and reported in line with PRISMA reporting guidelines. Results: Seroprevalence was significantly higher in the USA than in Latin America, independently of assay, patient cohort, methodological quality or study year (OR: 1.82 (1.06‐3.08), P = .03). Patients in the USA had a more than doubled estimated seroprevalence (up to 9%, confidence interval 5%‐15.6%) than those in Brazil (up to 4.2%, confidence interval 2.4%‐7.1%; OR: 2.27 (1.25‐4.13); P = .007) and Mixed Caribbean (up to 1%, OR: 8.33 (1.15‐81.61); P = .04). A comparison with published data from Europe demonstrated that anti‐hepatitis E virus seroprevalence in the USA and Europe did not differ significantly (OR: 1.33 (0.81‐2.19), P = .25), while rate in South America was significantly lower than that in Europe (OR: 0.67 (0.45‐0.98), P = .04). Conclusions: Hepatitis E virus is common in the USA. Surprisingly, the risk of hepatitis E virus exposure was low in many South American countries. Seroprevalence did not differ significantly between Europe and the USA. Hence, hepatitis E virus is not limited to countries with low sanitary standards, and a higher socioeconomic status does not protect populations from hepatitis E virus exposure.